Prolonged Posttreatment Virologic Control and Complete Seroreversion After Advanced Human Immunodeficiency Virus-1 Infection. (15th December 2020) - Uruena, Analia; Cassetti, Isabel; Kashyap, Neena; Deleage, Claire; Estes, Jacob D; Trindade, Christopher; Hammoud, Dima A; Burbelo, Peter D; Natarajan, Ven; Dewar, Robin; Imamichi, Hiromi; Ward, Addison J; et al.
Abstract: Background: Possible human immunodeficiency virus (HIV)-1 clearance has rarely been reported. In this study, we describe a unique case of an HIV-positive, combination antiretroviral therapy (cART)-experienced woman with prior acquired immunodeficiency syndrome (AIDS) who has not experienced viral rebound for over 12 years since discontinuing cART. Methods: Leukapheresis, colonoscopy, and lymph node excision were performed for detailed examination of virologic (including HIV reservoir) and immunologic features. Comparisons were made with chronically infected patients and healthy controls. Results: No HIV-specific antibodies were detected in serum. Plasma HIV ribonucleic acid (RNA) levels were <0.2 copies/mL, and, except for low-frequency HIV deoxyribonucleic acid (DNA) + cells in lymph node tissue (1 copy/3 × 10 6 cells), HIV antigen could not be detected by quantitative virus outgrowth (<0.0025 infectious units/10 6 CD4 + T cells) or by most measurements of HIV RNA or DNA in blood, lymph node, or gut-associated mononuclear cells. Human immunodeficiency virus-specific T-cell responses were detectable but low. Brain imaging revealed a prior biopsy site and persistent white matter disease since 1996. Human immunodeficiency virus DNA + cells in the 1996 brain biopsy specimen confirmed her identity and initial HIV diagnosis. Conclusions: This represents the first report of complete seroreversion, prolonged posttreatment virus suppression, a profoundly small HIV reservoir, and persistent HIV-specific T cells in an adult with prior AIDS.